Non-Genetic Factors Shaping Milk Composition in Early Lactation of Awassi Ewe - Shahla Fathola Hassan (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Milk composition in sheep is influenced by various genetic and environmental factors. Specific Background: Among these, non-genetic contributors during early lactation remain underexplored, particularly in the Awassi breed reared in Iraq. Knowledge Gap: Limited data exist on how ewe-related non-genetic factors influence key milk constituents over time postpartum. Aims: This study aimed to evaluate the effect of ewe age, lamb sex, birth type, and body weight on milk fat, lactose, protein, and solid-not-fat (SNF) concentrations during early lactation in Awassi ewes. Results: In a 4 × 2 × 2 × 3 factorial design using 50 ewes, milk fat declined from day 10 (8.55%) to day 30 (7.23%) before rebounding, while lactose remained stable ( 4.3%), and both SNF and protein increased gradually. Young ewes had higher fat, whereas four-year-olds had the least. Twin births were associated with lower fat but higher lactose and SNF. Heavier ewes showed elevated SNF at later stages. Lamb sex had no significant impact. Negative correlations were observed between fat and both lactose and SNF. Novelty: This study is among the first to quantify time-specific effects of multiple non-genetic factors on Awassi milk traits. Implications: These findings underscore the importance of managing ewe-specific variables to enhance milk quality in Awassi sheep husbandry. Highlights: Non-genetic factors such as ewe age, birth type, and body weight significantly shape milk traits. Fat decreases mid-lactation, while protein and SNF steadily increase. Findings provide management insights to improve ovine dairy quality in semi-arid regions. Keywords: Awassi Ewes, Milk Composition, Non-Genetic Factors, Early Lactation